The Ability of Ece Teachers to Use ICT in The Industrial Revolution 4.0 - Rohita Rohita (LPPM Universitas Pahlawan Tuanku Tambusai, 2020)
This research is conducted with the aim to determine the ability of early childhood education teachers to use ICT in the industrial revolution 4.0. The qualitative method is used with data collection techniques in the form of surveys and data analysis using descriptive statistics. The subjects of the study were 26 early childhood education teachers in South Jakarta and Tangerang city. The results showed that early childhood education teachers are able to utilize information and communication technology for the sake of organizing educational development activities quite well. ICTs are used to find references, examples of learning media, look for examples of activities according to themes and sub themes, as well as preparing learning plans and assessments. Improvements need to be made in an effort to operate the computer to be better because there are still teachers who are awkward in interacting with computers because the ability to operate computers is not optimal and the lack of availability of computers in adequate numbers.